Factores socio demográficos y de estilos de vida asociados a un bajo nivel de actividad física durante el confinamiento producto del COVID-19 en adultos latinoamericanos - Cigarroa, Igor; Bravo-Leal, Michelle; Zapata-Lamana, Rafael; Pavón-León, Patricia; Herrera, Carlos; Guzmán-Muñoz, Eduardo; Alonso-Palacio, Luz Marina; Borja-González, Juana (Revista Médica de Chile, 2021)
Background: The confinement caused by the COVID-19 pandemic changed the lifestyles of the population affecting their levels of physical activity. Aim: To determine the factors associated with a low level of physical activity in adults during confinement during the COVID-19 pandemic. Material and methods: Adults from Chile, Colombia, México and Perú were invited through social networks to answer an online survey. Questions about sociodemographic, health status and lifestyle variables were included. The level of physical activity and sedentary behavior were determined through the short version of the International Physical Activity Questionnaire (IPAQ). Results: The survey was answered by 3362 adults aged between 18 and 60 years. Respondents more likely to be inactive were women, those with less than eight years of education, those with overweight or obesity, those who smoked at least one cigarette a day, consumed alcohol four or more times a week, slept less than six hours per day and spent more than 6 hours per day in sedentary behaviors. Conclusions: These findings provide a sociodemographic and lifestyle profile associated with physical inactivity during the period of confinement in Latin American adults. The results confirm the need to promote healthy lifestyles in the population during periods of confinement.